Oral Health Condition Among Selected School Children in Dhaka City (Bangladesh Journal of Dental Research & Education, 2013)
This was a cross-sectional study on oral health conditions among selected school children in Dhaka city, this study was conducted at Ideal kinder garten and high school situated at kamarpara, Dhaka. The study was carried out among 200 children aged between 6-15 years from the month of September to December 2012. The main objective of the study was to assess the oral health conditions of school children through decayed, missing and filled teeth (DMFT) status of their teeth. Data were collected with a pretested structured questionnaire and a checklist. On analysis of data it was found that among the 200 children 101 (51%) were male and 99(49%) were female, tooth brushing twice daily 140(70%) was in comparison to once daily 60(30%). Tooth brushing before breakfast was 100(50%), after breakfast 20(10%),after dinner 80(40%). Tooth paste was used by most of the respondents 152(76%), than tooth powder 48(24%). Tooth brush was used by all of the respondents 200(100%). Among 200 respondents 69(35%) having no plaque,112(56%) had mild accumulation and 19(9%) had moderate plaque accumulation. Among 200 children 18(9%) did not have any decayed tooth, 30(15%) had only 1 tooth decay, 78(39%) had 2 teeth decay, 20(10%) had 3 teeth decay, 44(22%) had 4 teeth decay, while 10(5%) had more than 4 teeth decayed. Among 200 children 34(17%) did not have any missing tooth, 46(23%) had only 1 tooth missing, 85(43%) had 2 teeth missing, 20(10%) had 3 teeth missing, 15(7%) had 4 teeth missing, while none had more than 4 teeth missing. Among 200 children 32(16%) did not have any filled tooth, 66(33%) had only 1 tooth filled, 60(30%) had 2 teeth filled, 24(12%) had 3 teeth filled, 18(9%) had 4 teeth filled, while none had more than 4 teeth filled. Among 200 respondents 118(59%) had normal gingival condition while 82(41%) had red swollen gingiva. On the basis of the finding it was concluded that dental caries in children is a major health concern and creating awareness among the public about their own and their childrens oral health through appropriate plan and policy can reduce the burden of dental diseases. Moreover mass media and general education of the people can play vital role in this regard.DOI: http://dx.doi.org/10.3329/bjdre.v3i1.16591 Bangladesh Journal of Dental Research & Education Vol.3(1) 2013: 21-24